Arginine-Glycine-Aspartic Acid Motif Is Critical for Human Parechovirus 1 Entry - Boonyakiat, Yingmanee (American Society for Microbiology, 2001)
The human parechovirus 1 RGD motif in VP1 was studied by mutagenesis. An RGD-to-RGE change gave only revertant viruses with a restored RGD, while deletion of GD was lethal and nonrevertable. Mutations at the +1 and +2 positions had some effect on growth properties and a +1 M-to-P change was lethal. These studies indicate that the RGD motif plays a critical role in infectivity, presumably by interacting with integrins, and that downstream amino acids can have an influence on function.